Language Shift and Cultural Transformation: Globalization’s Influence on Local Identity in Banjar, Pandeglang - Nupus, Hayati (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2025)
This study aims to examine language shift and cultural transformation as an impact of globalization on the local identity of the Banjar community in Pandeglang. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis to understand how globalization affects language use and cultural practices in the community. The results show a significant language shift from Banjar to Indonesian and English, especially among the younger generation. This shift is influenced by educational factors, mass media, digital technology, and socio-economic needs that demand broader and more modern language skills. In addition, the cultural transformation that occurs reflects the community's adaptation to global influences through the incorporation of traditional and modern elements, thus forming a dynamic hybrid cultural identity. Nevertheless, the Banjar community continues to preserve the local language and culture through local language education, the implementation of modified customary traditions, and the use of digital technology for cultural documentation and promotion. This research confirms that globalization has a complex impact on local language and culture, threatening the sustainability of local identity but also opening opportunities for cultural innovation and adaptation. The implications of this research are important for the development of adaptive language and culture preservation strategies, as well as the strengthening of local identity in the global era. Future research prospects can focus on the development of a preservation model based on community participation and the utilization of digital technology as an effective medium for preserving local culture.